Evaluating the Effect of Palm Oil Planting Material Characteristics on the Population of Weevil Pollinator (Elaeidobius kamerunicus) - Wahyuni, M.; Wagino, .; Manurung, Hilman (Cutting-edge Research in Agricultural Sciences Vol. 6, 2021)
The productivity of oil palm plants is determined by the success of pollination. Some factors that influence are the planting material, rainfall conditions and the adequacy of pollinating weevil, namely Elaeidobius kamerunicus (EK). Oil palm plants are monoecious with separate male flower inflorescence and female flower inflorescence with flowering sequences and ripening phases that never overlap so that the nature of the pollination is cross pollination. Producers of planting materials produce crosses of Dura X Pisifera hybrids with their spesific characters. This research aim was to determine the effect of planting material on flowering characteristics and EK population. The research was conducted in Adolina (DxP Simalungun) and Dolok Ilir (DxP La Me) in January 2018 - October 2018 with a descriptive method. The research results showed that the character of oil palm planting material affected the number and character of male flowers as a source of pollen.In planting material with a large number of male flower spikelet, the DxP Simalungun has a positive effect on the population of Elaedobius kamerunicus. The efforts to increase the EK can be achieved by applying the Hatch and Carry technique which can increase EK populations by 32-45%.